Evaluation of the collection of periodicals Specialized Library Clemencia Rabbit Chacón, School of Human Movement Sciences and Quality of Life, National University (Costa Rica) - Montero Cordero, Paula Marcela (2012)
The Specialist Library Clemencia Rabbit Chacón, School of Human Movement Sciences and Life Quality of the National University of Costa Rica is a unit of information and scientific-technical sport. The collection includes texts on various subjects such as physical education, sport science, recreation, sports medicine, sports psychology, sports sociology and sports journalism.Born as a library in 1969, on the initiative of a group of teachers and students of the School, was one of the first type, both nationally and in Central America. At its inception, received funds donated by several teachers and the embassies of Spain, the U.S. and Mexico. This center provides information resources for academic, research, extension and production, in order to strengthen and consolidate a system of higher education professionals in the field of sports science.